Pharmacogenomic of warfarin and its implication on international normalized ratio and dosing: A narrative review - Wicaksono, Agil Wahyu; Selma Mutiara Hani (Indonesian Journal of Pharmacology and Therapy, 2024)
Genotype is an important factor in warfarin dosing requirements and affects the risk of excess anticoagulant use due to its narrow treatment window, high drug interactions, and frequent bleeding. The CYP2C9 and VKORC1 genotypes have a strong and consistent association with warfarin dose requirements, and the algorithms of dosing incorporating genetic and clinical information are stable warfarin dose predictions. The review article aimed to investigate the association between the genotype of CYP2C9 and VKORC1 and the current relevant dosing recommendations for warfarin in various patients. The secondary purpose was to correlate genotype with the international normalized ratio (INR). It was a narrative review of the most recent reference (observational, trial study, and RCT) on the clinical application of pharmacogenomic testing for warfarin pharmacokinetics and pharmacodynamics and its impact on INR over the last 5 yr from the PubMed and SAGEPub databases. Six studies were included in this review and showed how the genetic polymorphisms and dosage responses of different groups differed. Pharmacogenetic algorithms meet non-inferior and superior criteria for reducing dose titration compared to traditional dosing approaches, and predict actual maintenance doses well. Bleeding mostly occurred in the first mo of treatment, with no significant difference in the frequency of total bleeding between groups. Genotype-based dosing of warfarin increased the proportion of time in the therapeutic INR range (% TTR) and reduced the time to reach a therapeutic INR. Administration of CYP2C9 and VKORC1 genotypes based on warfarin may be beneficial in patients with atrial fibrillation, mechanical valve replacement, and bleeding prophylaxis for hip or knee arthroplasty. Stable warfarin doses were achieved in statistically more patients in the genotype-targeted group (47%) than in the traditional group (22%).